Predicting cholangiocarcinoma in patients with primary sclerosing cholangitis before transplantation. Issue 11 (November 1991) - Miros, M; Kerlin, P; Walker, N; Harper, J; Lynch, S; Strong, R
Abstract : Patients with primary sclerosing cholangitis are at an increased risk of developing cholangiocarcinoma, which is difficult to diagnose because the biliary tree is already distorted. Eleven patients with primary sclerosing cholangitis who underwent orthotopic liver transplantation at this hospital were evaluated. Four patients had coincidental histologically proved cholangiocarcinoma. Patients with cholangiocarcinoma in contrast to patients without tumour presented with rapid onset of persistent jaundice, pruritus, and weight loss associated with an appreciable rise in bilirubin (8x v 2x) and alkaline phosphatase (3.5x v 1.2x) over one year. Cholangiography and computed tomography showed appreciably dilated intrahepatic bile ducts (3/4 v 0/7). The diagnosis of cholangiocarcinoma could only be established before operation in one patient by fine needle aspiration cytology. Tumour was recognised at operation in one other. Histological examination of hepatectomy specimens showed that patients with cholangiocarcinoma had less advanced histological features of primary sclerosing cholangitis. Multiple areas of carcinoembryonic antigen positive epithelial atypia and carcinoma in situ were found in all patients with cholangiocarcinoma. Cholangiocarcinoma recurred in two patients at 14 and 39 months after transplantation. Superimposed cholangiocarcinoma can be predicted in most patients with cholangitis before transplantation, although a definitive diagnosis is difficult to make. Their prognosis after successful transplantation is guarded.